Smart Techniques for Fault Diagnosis in Power Transformer. Issue 1 (1st March 2022) - Sharma, Naveen Kumar; Bhalla, Deepika; Manisha,; Kaur, Kulraj
Abstract: In a power network installed transformers are among the most expensive equipment. Outage of a transformer causes substantial financial loss not only due to the cost involved in repair or replacement, but also due to loss of revenue until corrective action is taken. To avoid the financial and reliability loss in the past two decades the monitoring of in-service transformer health has become obligatory for the utilities. The tests that were earlier done were to assess the dame of permanent nature. However, it has been known for quite some time that system abnormalities, switching. Loading, ambient conditions contribute to accelerated aging that results in sudden failure or incipient faults. Monitoring the condition of in-service equipment can always reduce failure risk. For early detection of fault dissolved gas analysis, furan analysis and degree of polymerization are the recent techniques that are becoming prevalent. A real-time assessment of the transformer condition using these techniques is an important tool for enhancing system reliability.